TROUBLE SHOOTING DURING BIOANALYTICAL ESTIMATION OF DRUG AND METABOLITES USING LC-MS/MS: A REVIEW - K.K.Sharma; Man Mohan Singhal; Ganesh N. Sharma; Jyotsana Sanadya (Wolters Kluwer Medknow Publications, 2010)
Bioanalysis frequently involves the measurement of very low analyteconcentrations in complex and potentially variable matrices. An initial attempt has beenmade to apply a risk management tool to the bioanalytical method development likeselection of spiked plasma volume, selection of internal standard to minimize processingerror, selection of medium and extraction procedure, setting of mobile phase and pH,determination of chromatographic conditions etc. and to minimize instrumental errorlike; ion suppression and matrix effect.